The Judgment Of The Criminal Action Of Narcotics In Islamic Law Perspective And Human Rights Protection - Eka Santosa (Universitas Islam Sultan Agung, 2020)
The formulations of the problems in this research are: What is the basis for the judge's consideration in making a decision regarding the crime of narcotics abuse in the Pekalongan District Court? And how is the court's decision regarding narcotics crime based on the decision of the Pekalongan District Court from the perspective of Islamic law and protection of human rights human?The research carried out in this thesis is normative legal research, namely research on problems by looking at the prevailing regulations. The approach method used is normative legal research which is literature research, namely research on secondary data.The results of the research were as follows: Whereas narcotics crime is a crime, for this reason, a set of laws that regulate criminal sanctions for narcotics abuse is needed, namely: Law No. 35 of 2009 concerning Narcotics. The purpose of making Law No. 35 of 2009 concerning Narcotics is to prevent the occurrence of narcotics abuse and to eradicate illicit narcotics trafficking. The formulation of offenses in the aforementioned law focuses on the abuse and distribution of narcotics starting from cultivation, production, distribution, traffic to the users, not on assets obtained from criminal acts. The basis for consideration of judges in making decisions are: Judgments of a judicial nature, considerations of a non-judicial nature, and things that are burdensome and alleviate the crime. Judges must not only be based on statutory regulations, but must pay attention to the general feelings and opinions of the community.Keywords: Narcotics Crime, Islamic Law, Human Rights